Cell-Based Therapies: Ferromagnetic Versus Superparamagnetic Cell Targeting - Tasneem Halhouli; Lisa Münchhalfen; Sarkawt Hamad; Larissa Schmitz-Ullrich; Frank Nitsche; Felix Gaedke; Astrid Schauss; Linlin Zhang; Quoc-Khanh Pham; Gang Bao; Kurt Paul Pfannkuche (Bioengineering)
Stem-cell-based therapies rely on the transplantation of stem cells or stem-cell-derived organotypic cells into injured tissues in order to improve or restore tissue function that has been impaired by various diseases. The potential of induced pluripotent stem cells has created many applications in the field of cell therapy, for example. Some applications, for example, those in cardiac cell therapy, suffer from low or very low efficiencies of cell engraftment. Therefore, magnetic cell targeting can be discussed as a method for capturing superparamagnetic nanoparticle-labelled cells in the tissue. Here, we employ superparamagnetic iron oxide nanoparticles (SPIONs) for the intracellular magnetic loading of mesenchymal stem cells (MSCs). In addition, we test a novel strategy of labelling MSCs with ferromagnetic particles. The adhesion assays demonstrate a faster adhesion kinetic of SPIONs-loaded MSC spheroids when a magnetic field was applied, resulting in >50% spheroid adhesion after 30 min. Clustering of cells inside the magnetic field is a second potential mechanism of magnetic cell retention and >80% of cells were found to be aggregated in clusters when placed in a magnetic field for 10 min. SPIONs-loaded and ferromagnetic-particle-loaded cells performed equally in the cell clustering assay. In conclusion, the clustering of SPION-labelled cells explains the observation that magnetic targeting reaches maximal efficiency in vivo after only 10 min of magnetic field application. This has significant implications for magnetic-targeting-assisted stem cell and cell replacement therapies.